2019
DOI: 10.1177/1477971419896375
|View full text |Cite
|
Sign up to set email alerts
|

Development of a continuous professional development training module based on multicultural counselling competency for professional counsellors in Malaysia

Abstract: The aim of this study was to develop a continuous professional development training module based on multicultural counselling competency for professional counsellors in Malaysia. The research methodology comprised three phases: (i) training need assessment using survey method, (ii) module design and development and (iii) module evaluation using an experimental design. First, the Multicultural Counselling Competency Survey-Malaysian Counsellor Edition questionnaire was used to collect data from 116 professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The table shows that the stability coefficient for the subscales of the tool was high. These results were acceptable for the study since the stability factor is greater than 70% [33].…”
Section: Stability Of the Scale/questionnaire 331 Cronbach's Alphamentioning
confidence: 78%
“…The table shows that the stability coefficient for the subscales of the tool was high. These results were acceptable for the study since the stability factor is greater than 70% [33].…”
Section: Stability Of the Scale/questionnaire 331 Cronbach's Alphamentioning
confidence: 78%
“…Further, Sidek's Module Development Model (SMDM) is a comprehensive and robust model that has specific steps to develop a module and assess its validity and reliability. Several other local studies have also applied Sidek's model when developing a mental health module and all their studies showed promising results (32,33,43). However, the CTSEE module must be administered by a registered professional counsellor in order to safeguard the clients' wellbeing and maximize its effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from that, there is a need for more continuous development programs in the field of professional counselling in the Malaysian context (43). Therefore, this module can be promoted among practising counsellors through training programs that will ensure that clients are provided with high-quality counselling services.…”
Section: Recommendations and Implications For Counselling Practicementioning
confidence: 99%